2014 IEEE International Ultrasonics Symposium 2014
DOI: 10.1109/ultsym.2014.0093
|View full text |Cite
|
Sign up to set email alerts
|

Technological process and resonator design optimization of Ir/LGS high temperature SAW devices

Abstract: Photolithography together with ion beam etching was used for fabrication of high temperature SAW devices. Ir thin film of 0.3 µm thick was deposited by magnetron sputtering without additional adhesion layers and than Ir film was annealed after electrode patterning in different conditions. The resistivity of magnetron sputtered thick Ir films drops noticeably after annealing. However, this process requires special care in order to avoid delaminating of the film due to developing high stress during such procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
0
6
0
1
Order By: Relevance
“…Micromachines 2021, 12, 643 2 of 8 et al [14] and Aubert et al [15,16] prepared Ir-based composite electrodes and demonstrated their stable operation above 800 °C. Alternatively, Moulzolf et al [17] prepared Pt-ZrO2 and Pt-HfO2 composite electrodes that operated stably for 4 h at 1000 °C.…”
Section: Sensor Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…Micromachines 2021, 12, 643 2 of 8 et al [14] and Aubert et al [15,16] prepared Ir-based composite electrodes and demonstrated their stable operation above 800 °C. Alternatively, Moulzolf et al [17] prepared Pt-ZrO2 and Pt-HfO2 composite electrodes that operated stably for 4 h at 1000 °C.…”
Section: Sensor Fabricationmentioning
confidence: 99%
“…For example, Thompson [13] found that metal films agglomerate at high temperatures, resulting in a loss of electrical conductivity. In addition, Sakharov et al [14] and Aubert et al [15,16] prepared Ir-based composite electrodes and demonstrated their stable operation above 800 • C. Alternatively, Moulzolf et al [17] prepared Pt-ZrO 2 and Pt-HfO 2 composite electrodes that operated stably for 4 h at 1000 • C. In addition, Aubert et al [18][19][20][21] used Ta as the adhesive layer in the electrode to prepare a SAW device capable of stable operation at 1000 • C for at least 30 min.…”
Section: Introductionmentioning
confidence: 99%
“…All these problems are waiting to be taken care of. However, greater conductance of thicker electrodes is obvious and better device properties, such as a larger resonator Q-factor have already been demonstrated [22].…”
Section: Electrode Materials Selectionmentioning
confidence: 99%
“…Except for their important roles in nanocatalyst, [18,19] the multilayer metal films and alloys present their effect on high-temperature film electrodes. For example, alloys of different compositions have been found to have more stable conductivity at high temperatures [20][21][22][23][24]. In addition, Ti or Ta adhesion layers, [25][26][27][28][29][30] capping layers, [31] buffer layers, [15] and diffusion barriers [32][33][34] have also been applied to promote the hightemperature stability of electrode resistivity.…”
Section: Introductionmentioning
confidence: 99%